KALANJANA GRASS PRODUCTIVITY IN BUNDER GRAND FOREST PARK COMMUNITY ZONE - Muhibun Khanam; Sabiqul Marom; Anggie Saputri; Ariq Zaidan; Izmi Jaatsiyah; Lelita Gian Widiya Arista; Siti Zahra; Yus Andhini Bhekti Pertiwi; Ana Agustina; Harish Faza (Jurnal Belantara, 2026)
Bunder Grand Forest Park is one of the conservation areas that serves as a source of sustenance for surrounding communities by implementing agroforestry initiatives within the Community-Use Zone. Although previous studies have confirmed the biophysical suitability of this site for kalanjana grass (Brachiaria mutica) cultivation, no study has established quantitative productivity data across the five Forest Farmer Group (KTH) management units, leaving a critical gap in the empirical basis needed for sustainable harvest management and carrying capacity assessment. This study addresses this gap by quantifying the productivity of kalanjana grass (Brachiaria mutica) across five farmer groups in the Community-Use Zone of Bunder Grand Forest Park. Field observations were conducted using 30 1×1 m plots to measure plant height, leaf number, and fresh weight, while interviews with 30 respondents collected data on land management practices and economic valuation. Grass cultivation practices and productivity were assessed using descriptive analysis of interview and observation data. Results showed that productivity varied considerably across KTHs: KTH Langgeng recorded the highest yield at 98,856 kg/ha/year (IDR 49,428,000/ha/year), followed by KTH Puntuk Srumbung (74,808 kg/ha/year; IDR 37,404,000/ha/year), KTH Wana Makmur (48,630 kg/ha/year; IDR 24,315,000/ha/year), KTH Ngreksobawono (40,590 kg/ha/year; IDR 20,295,000/ha/year), and KTH Ngudi Lestari (32,605.71 kg/ha/year; IDR 16,302,857/ha/year). Productivity variation across KTHs was influenced by biophysical site conditions and farmers' socioeconomic characteristics. To optimize community empowerment, it is recommended to diversify the species and products cultivated by each KTH, while accounting for local environmental factors and upholding conservation principles.